Educational learning lab supporting innovation adoption in vocational education - Väljataga, Terje; Ümarik, Meril; Loogma, Krista; Bentsalo, Inna; Daukilas, Sigitas; Kaminskiene, Lina; Vaitkute, Lina; Gedviliene, Genute; Tutlys, Vidmantas (Frontiers in Education, 2025)
This article explores the implementation and sustainability of innovative educational practices in a joint collaborative research project involving Estonia and Lithuania. Four interventions following the Educational Learning Lab approach were designed to counteract drop-out from vocational education and training for young people at risk of social exclusion. The study investigates the conditions for vocational teachers' knowledge appropriation leading to sustainable innovation in the empowerment of vulnerable students. Through applying the Knowledge Appropriation Model to the design of intervention cases, data collection and analyses, the article discusses how knowledge maturation, scaffolding, and appropriation practices emerged during the Educational Learning Labs.